VALIDATION OF THE DIAGNOSIS BONE PAIN AND ITS NURSING INTERVENTIONS IN MULTIPLE MYELOMA - Luiz Fernandes Gonçalves Fialho; Patricia dos Santos Claro Fuly; Mauro Leonardo Salvador Caldeira dos Santos; Joséte Luzia Leite; Silvia Maria de Sá Basílio Lins (Universidade Federal do Paraná, 2014)
Descriptive study aimed at validating the nursing diagnosis Bone Pain in multiple myeloma and its nursing interventions. A bibliographic search was undertaken to construct the assertions and the International Classification for Nursing Practice®. Next, using a form, the assertions were submitted content validation by cancer nursing specialists active at a university hospital. The analysis was carried out through simple statistics, in view of the variable of interest: agreement level, with a result superior to 0.75. The diagnosis Bone Pain and the interventions reached an agreement rate of 1.0 and 0.90, respectively. The validation indicates the relevance of the nursing diagnosis in patients with multiple myeloma and reflects the possibility to improve the quality of care through standardized nursing interventions.